Environmental Considerations for Trauma‐Responsive Juvenile and Family Courts: A Review of the Literature with Recommendations for Practice. (1st June 2018) - DeVault, Alicia; Helfrick, Vanessa A.; Marsh, Shawn C.; Snider, Katie M.
Abstract: Juvenile and family courts serve some of our most vulnerable populations, many of whom have experienced some traumatic event. People suffering with posttraumatic stress disorder (PTSD) are known to be more sensitive to environmental stimuli, and many of the environmental conditions within courts can be challenging for those suffering traumatic stress. Trauma‐responsive practices help foster conditions of healing, which can benefit both the court user and those who work within the court. Research reviewed in this article demonstrates the likelihood of negative behavioral and emotional responses to specific environmental factors for people suffering PTSD and other stress reactions, and offers recommendations to minimize environmental stressors.